Experiencing digital technologies: The importance of feeling safe in healthcare – A qualitative participatory design - Minartz, Peter; Vondeberg, Carmen; Obert, Laura; Bleck, Christian; Hemming, Bernhard; Vöcking, Mara; Ose, Claudia; Znotka, Matti; Cürlis, Diana; Karrenbrock, Anne; Oehmichen, Frank; Heistermann, Peter; Kuske, Silke (Das Gesundheitswesen, 2025)
Digital technologies are increasingly used in healthcare. In this context, perceived safety plays a critical role in their acceptance and implementation. Previous research had focused more on data security or specific digital technologies. There has also been a lack of participatory approaches to consider and empower healthcare recipients (and relatives), providers, and technology experts to broaden the phenomenon.The aim of this study was to present a comprehensive perspective on the needs, influencing factors and related outcomes in the context of feeling safe with digital technologies in healthcare.A qualitative, exploratory, and participatory methodology was used with five guide-based focus group workshops. Each workshop explored one of five digital technology demonstrations provided at the beginning: (1) electronic health records (EHR), (2) robotics, (3) artificial intelligence (AI), (4) smart home, and (5) smart hospital. All participants were invited for a guide-based discussion. The study focused on the levels of ‘involvement’ and ‘collaboration’ by also empowering participation. The workshop target groups were actively involved in the development and execution of the workshops and were empowered. The data were analysed via a content analysis approach, with a mostly inductive procedure.Feeling safe was found to affect thoughts, emotions, and actions. For example, a higher level of perceived safety increased the acceptance of digital technologies, whereas a lower level of perceived safety decreased it. The corresponding needs and influencing factors differed in terms of their scope and focus depending on the context. The aspect of ‘control’ was most frequently addressed by all the target groups and was viewed as relevant in all the workshops. In general, digital technologies were viewed as supplements rather than substitutes for healthcare providers.This study extends beyond the current state of research on perceived safety and the use of digital technologies in healthcare by providing a comprehensive overview of the corresponding needs and influencing factors at various levels, such as the individual, community-organizational, and system-society levels. The perceived safety of healthcare recipients and providers related to digital technologies should be taken into consideration to achieve positive implementation outcomes.
Keywords: emotional safety; psychological safety; digital technologies; participatory research; digitalization